2014
DOI: 10.1055/s-0034-1368569
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Vaccinium Species by Chemical Fingerprinting Based on NMR Spectra, Validated with Spectra Collected in Different Laboratories

Abstract: A method was developed to distinguish Vaccinium species based on leaf extracts using nuclear magnetic resonance spectroscopy. Reference spectra were measured on leaf extracts from several species, including lowbush blueberry (Vaccinium angustifolium), oval leaf huckleberry (Vaccinium ovalifolium), and cranberry (Vaccinium macrocarpon). Using principal component analysis, these leaf extracts were resolved in the scores plot. Analysis of variance statistical tests demonstrated that the three groups differ signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Despite the 10-year consistency of the findings, it is important to realize that repetition of any LC-based analysis requires revalidation due to its dependence on numerous instrument-related factors, particularly those related to (non)linearity of the detectors (UV, MS), the injector system, and the characteristics of the columns. This does not apply to qHNMR methods: once established, they can be rerun anytime later, provided the NMR instrument is validated per se, 39 and the qHNMR acquisition parameters are identical or demonstrated to be congruent between the different hardware and magnetic fields used. Another unique advantage of qHNMR is that additional analytes can be included even years later when peak assignments have become available, to study the same sample or the original FID of the qHNMR measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the 10-year consistency of the findings, it is important to realize that repetition of any LC-based analysis requires revalidation due to its dependence on numerous instrument-related factors, particularly those related to (non)linearity of the detectors (UV, MS), the injector system, and the characteristics of the columns. This does not apply to qHNMR methods: once established, they can be rerun anytime later, provided the NMR instrument is validated per se, 39 and the qHNMR acquisition parameters are identical or demonstrated to be congruent between the different hardware and magnetic fields used. Another unique advantage of qHNMR is that additional analytes can be included even years later when peak assignments have become available, to study the same sample or the original FID of the qHNMR measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative NMR (qNMR) is another technique which provides chemical ngerprinting capable of distinguishing species and authenticating botanical origins. 67 The relative intensities, retention times, and spectroscopic data obtained by chromatographic analysis can be used to putatively identify a sample. Small molecules are more stable than DNA, and they typically survive the processing involved with preparing botanical natural products.…”
Section: Authentication By "Chemical Ngerprints"mentioning
confidence: 99%
“…Methods can be validated both within a single laboratory (intralaboratory validation) 95,194 or across multiple laboratories (interlaboratory validation). 67,90 The International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) provides general guidelines for validation of analytical methods, 195 and more specic guidelines and denitions related to validation of constituents of botanicals have been draed by a subcommittee of AOAC INTERNATIONAL. 13,193 When selecting a method for analysis of botanicals, we recommend reviewing multiple published methods (if available), with particular attention to those that have been validated.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Vaccinium extracts, including those from V. angustifolium, are a rich source of phenolic compounds (Harris et al, 2007;Hicks et al, 2012;Markus et al, 2014;McIntyre et al, 2009) and have been shown to influence cell migration and invasion using in vitro models of cancer metastasis (Adams et al, 2010;Matchett, MacKinnon, Sweeney, Gottschall-Pass, & Hurta, 2005), in vitro models of endothelial cell migration and invasion (Tulio et al, 2012), and animal models of wound healing (Nayak et al, 2010). In this study, the .…”
Section: Discussionmentioning
confidence: 99%